1982
DOI: 10.1103/physrevlett.48.1610
|View full text |Cite
|
Sign up to set email alerts
|

Instability Cascades, Lotka-Volterra Population Equations, and Hamiltonian Chaos

Abstract: When an instability mode which is driven unstable can have its growth reversed because it is depleted by driving (pumping) another similar mode via a three-mode interaction, and when that process can be repeated over several pump modes, one can speak of an instability cascade. If the modes that are not acting as pumps are heavily damped (as in nonlinear Landau damping for plasma waves), the relative phases have no interesting behavior and the equations for the* mode actions are a particular case of the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Nonetheless, also in this situation, for an even number of species with n ≥ 4 it was demonstrated that Eq. (1) can display chaotic behavior resembling Hamiltonian chaos [10]. We also mention that when three or more species are in cyclic competition according to a dynamics described by Eqs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, also in this situation, for an even number of species with n ≥ 4 it was demonstrated that Eq. (1) can display chaotic behavior resembling Hamiltonian chaos [10]. We also mention that when three or more species are in cyclic competition according to a dynamics described by Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…Since Lotka and Volterra's seminal and pioneering works [1,2], many decades ago, modeling of interacting, competing species has received considerable attention in the fields of biology, ecology, mathematics [3,4,5,6,7,8,9,10,11,12,13,14,15], and, more recently, in the physics literature as well [16,17,18,19,20,21,22,23,24,25,26,27]. In their remarkably simple deterministic model, Lotka and Volterra considered two coupled nonlinear differential equations that mimic the temporal evolution of a two-species system of competing predator and prey populations.…”
Section: Introductionmentioning
confidence: 99%
“…and find two relationships of the form (12). Clearly this is not possible in this case, as anticipated in Section 2.…”
Section: Examplesmentioning
confidence: 65%
“…As a final example we consider the Lotka-Volterra [4,10,12], [13]- [15] and Generalized Lotka-Volterra [6,7] structures of the form…”
Section: Examplesmentioning
confidence: 99%
“…dynamics (for either Lotka-Volterra 11 or generalized Lotka-Volterra 8 systems), plasma models19 and systems such as the Toda and relativistic Toda lattices 15. The interested reader is referred to the primary reference for further examples and the full details regarding issues such as the determination of the Casimir invariants and the reduction to the Darboux canonical form for separable Poisson structures 31.…”
mentioning
confidence: 99%